Genetic characteristics analysis of influenza A(H1N1) virus in Jiaxing, China, in the postepidemic era - Yin Song; Xue Zhang; Jimei Ji; Lina Li; Yamei Zhou; Ganglin Ren; Shencong Lv; Xiaofei Zhang; Yong Yan; Guoying Zhu (BMC Infectious Diseases)
Abstract Background Following the lifting of COVID-19 pandemic control measures, a progressive increase in influenza A virus activity, particularly the H1N1 subtype, has been observed in Jiaxing. This study systematically characterized the genomic evolution of influenza A(H1N1) viruses circulating in Jiaxing, China during the 2023–2024 epidemic seasons through whole-genome sequencing and phylogenetic analysis. Methods Viral RNA was detected by quantitative real-time PCR (qPCR) and 83 influenza A(H1N1) isolates (48 from 2023 and 35 from 2024 surveillance) were selected for whole-genome sequencing. Launch RDP4, MEGA11 and iTOL were used to analyze the homology, molecular evolutionary clusters and resistance sites of influenza A(H1N1) virus. Results The positivity rates of influenza A(H1N1) virus in Jiaxing were 10.66% in 2023 and 5.09% in 2024, respectively. Compared with vaccine strain A/Wisconsin/67/2022, the influenza A(H1N1) virus in 2023 and 2024 showed high homology, with the nucleotide homology of hemagglutinin gene ranging from 97.9% to 99.2% and that of neuraminidase gene ranging from 98.3% to 99.1%. Among 83 Jiaxing strains, 80 were classified as clade 6B.1A.5a.2a and 3 were assigned to clade 6B.1A.15a.2a.1. These strains were further categorized into subclades C.1 (45), C.1.9(17), C.1.9.3 (18), and D (3). Additionally, an HA/NA reassortant strain (A/ZJNH/SWL1331/2023) was identified in 2023, followed by an oseltamivir-resistant strain (A/ZJPH/SWL1544/2024) carrying the H275Y substitution in 2024. A total of 31 amino acid substitutions were identified in the HA1 segment of Jiaxing influenza A(H1N1) strains, affecting three antigenic sites: Ca (S137P, A139D, A141T/V, R142K, D222G), Cb (L70F, S71F), and Sb (I185S, D187N, S190G), plus an additional Ca1 substitution (K169Q). Conclusions During 2023–2024, multiple genomic sites of influenza A(H1N1) viruses in Jiaxing have acquired mutations, underscoring the need for enhanced continuous surveillance and prevention of H1N1 influenza.